PENDAMPINGAN PELATIHAN KEWIRAUSAHAAN BERBASIS SMARTPHONE GENERASI MUDA KEPADA KELOMPOK ANGGOTA KOPERASI KSPPS NURI PAMEKASAN - Azis Ashari (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2026)
This activity adopts a Participatory Action Research (PAR) approach, implemented through iterative cycles of observation, reflection, and collaborative action. The program actively involves youth as facilitators and cooperative members as participants, supported by Training of Trainers (ToT) sessions that equip the core KSPPS NURI team to disseminate knowledge on digital financing, sharia literacy, and entrepreneurship. Program outcomes show a 180% increase in digital financing disbursement during 2023–2025, driven by the use of the KSPPS NURI Mobile application, bank transfers, and digital wallets, alongside an 85% level of program independence without external dependency. Members’ digital and financial literacy improved significantly, reducing reliance on cash transactions and increasing operational efficiency, in line with the Sustainable Development Goals of poverty reduction and inclusive economic growth. Youth engagement strengthened social solidarity, enhanced UMKM competitiveness, and reinforced sharia compliance. For future development, the study recommends a tripartite partnership involving universities, cooperatives, and local governments to optimize and replicate hybrid financial inclusion models across East Java.